2016
DOI: 10.11118/actaun201664010333
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Farm Size in the Evaluation of Labour Productivity in Agriculture

Abstract: The paper deal with the analysis of diff erence in labour productivity of farms categorised according to their size, to determine if the set subsidy system infl uences labour productivity in the size groups of the farms. The source of data for enterprises analysis was the fi rms database, which contains accounting data of 926 farms with at least one employee. The observed data were from the 6 year period (2007)(2008)(2009)(2010)(2011)(2012). The farms were divided, according to their size into four categories … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 19 publications
(16 reference statements)
1
11
0
Order By: Relevance
“…These factors describe the economic importance and structural features of agriculture, resources and quality-of-production factors and the relationships between them, as well as the level of development of the country and agriculture. The importance of structural conditions for the increase in labour productivity, especially those expressed in the structure of farms and the level of employment in this sector, are emphasised by Polyzos and Arabatzis (2006) and Novotná and Volek (2016). It is worth noting that the level of agricultural labour productivity is influenced not only by the size of the labour force but also by the quality of labour resources related to human capital, which can be approximated by the level of education of farm managers (Giannakis and Bruggeman 2018).…”
Section: Methodsmentioning
confidence: 99%
“…These factors describe the economic importance and structural features of agriculture, resources and quality-of-production factors and the relationships between them, as well as the level of development of the country and agriculture. The importance of structural conditions for the increase in labour productivity, especially those expressed in the structure of farms and the level of employment in this sector, are emphasised by Polyzos and Arabatzis (2006) and Novotná and Volek (2016). It is worth noting that the level of agricultural labour productivity is influenced not only by the size of the labour force but also by the quality of labour resources related to human capital, which can be approximated by the level of education of farm managers (Giannakis and Bruggeman 2018).…”
Section: Methodsmentioning
confidence: 99%
“…It is noted that value of agricultural output has been significantly increased in Estonian, Latvian and Lithuanian farms, but despite these changes did not achieved those in the developed countries. Various studies have shown that the indicators can be defined as in various ways in assessing the impact of farm support programs and productivity as well (Novotna, 2016). As investment support in main new capital is one of the factors of competitiveness, and which may have a longer-term impact on productivity and resilience of farms in terms of competitive environment.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…In agreement with the study by Střeleček and Kollar (2002), it was determined that especially labour costs as the main item of fixed costs were reduced with increasing herd size. Similarly, the highest labour productivity was identified in large-sized farms in a study based on the accounting data of 926 Czech farms (Novotná and Volek, 2016). Increasing suckler herd size might therefore be of importance for achieving sufficient income and profitability (Gajos and Dymnicki, 2012).…”
Section: Economies Of Scalementioning
confidence: 99%